Maqashid Syariah And Digital Transformation In Public Services: A Case Study Of The Lubuklinggau Post Office - Heryaniputri, Wulandari; Rimbano, Dheo; Andrinaldo, Arisky; Azhar, Rudi (El-Ghiroh : Jurnal Studi Keislaman, 2025)
This study investigates the impact of digital transformation on the performance of the Lubuklinggau City Post Office, framed within the perspective of Maqashid Syariah. The introduction highlights the necessity of adapting to digital advancements in public services, emphasizing the importance of efficiency, ethical practices, and community welfare. As the digital era progresses, public institutions must evolve to meet the changing needs of society while adhering to fundamental Islamic values. The methodology employed in this qualitative research involved direct observations and interviews with employees and management at the Lubuklinggau City Post Office. The researchers aimed to gather insights into the current digital initiatives implemented and their effects on service delivery and employee performance. The data collection process was structured in two stages: initial observations to understand the general context, followed by focused interviews to extract specific information relevant to the research objectives. The results indicate that the Lubuklinggau City Post Office has successfully integrated various digital services, such as electronic payments and online tracking systems, which have significantly improved operational efficiency and customer satisfaction. Employees reported enhanced performance due to clearer regulations and the availability of digital tools that facilitate their tasks. However, challenges such as information literacy and the potential for misinformation in the digital landscape were also identified. In the discussion, the findings are analyzed through the lens of Maqashid Syariah, illustrating how the digital transformation aligns with the principles of protecting assets and promoting community welfare. The study concludes that while digital transformation presents challenges, it also offers substantial opportunities for enhancing public service delivery, provided that ethical considerations and community needs are prioritized. This research contributes to the understanding of how public institutions can navigate the complexities of digital transformation while remaining committed to their core values.